New security model for cross-realm C2C-PAKE protocol (Tongxin xuebao)
From the formalism point of view,the security attributes needed in the cross-realm C2C-PAKE scenario was first analyzed,and then a new security model for cross-realm C2C-PAKE was presented. Analogous to the general con-struction of 3PAKE protocol for single server C2C-PAKE setting,a general construction of cross-realm C2C-PAKE pro-tocol was given,which security was proved in the new security model.